Greenhouse Emissions and Climate Change : Implications for Developing Countries and Public Policy - Wheeler, David (World Bank, Washington, DC, 2017)
There is no longer any serious debate about whether greenhouse gas emissions from human activity are altering the earth's climate. There is also a broad consensus that efficient mitigation of emissions will require carbon pricing via market based instruments (charges or auctioned tradable permits). The remaining controversies stem mostly from economic and technological forecasting uncertainties, disputes about global and intergenerational equity, and political divisions over collective measures to combat climate change. Near term closure seems unlikely on any of these fronts, but the science is now sufficiently compelling that a global consensus supports concerted action. Developing countries must be full participants, because they will be most heavily impacted by global warming, and because the scale of their emissions is rapidly approaching parity with developed countries.